Pengaruh Modal Sosial terhadap Ketahanan Pangan Rumahtangga Petani di Desa Ciaruteun Ilir Kecamatan Cibungbulang Kabupaten Bogor - Sara Endarwati; Ekawati Sri Wahyuni (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
Social capital is an important component in a community. Social capital is used to help each other when in need, such as the need to secure food sufficiency in a household. Social capital consists of trust, networks, and social norms. Household food security is defined as a condition of food suffiency in one household in terms of availability, accesibility and consumability. This study aims to analyze the roles of social capital in household food security in Ciaruteun Ilir village, Cibungbulang subdistrict at Bogor Regency. The data collected by using a survey to 60 horticultural farmer houselds. The farmer’s household food security is not determined by socio economic level, spending level and the number of household members. Farmers use the capital social to generate income for buying foods.Keywords: social capital, food security, horticultural farmer